2007
DOI: 10.1051/fruits:2007013
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of cultivated almonds in Lebanon

Abstract: -Introduction. Although almond (Prunus dulcis L.) is one of the most important cultivated fruit trees in Lebanon, cultivated accessions have not yet been inventoried, and the identity of the varieties is unknown. Our study therefore aimed at assessing the genetic diversity of cultivated almonds in Lebanon using morphological characters. Materials and methods. Field surveys were performed in 2002-2003 with the aim of collecting different accessions of cultivated almond trees throughout the country. Thirty-six a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…The fruit fresh weights of Soury, Del and Abou chawkeh were substantially similar to values reported in the literature for the same varieties. 2 All the genotypes were deemed suitable for the production of oil, since, according to the classification proposed by Barranco-Navero et al 11 for the characterisation of olive varieties, the oil content was between medium and high, with Aayrouni having extremely high values. The highest fruit pulp/pit ratio measured in the variety Abou chawkeh confirmed that this variety is the best for table olive production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit fresh weights of Soury, Del and Abou chawkeh were substantially similar to values reported in the literature for the same varieties. 2 All the genotypes were deemed suitable for the production of oil, since, according to the classification proposed by Barranco-Navero et al 11 for the characterisation of olive varieties, the oil content was between medium and high, with Aayrouni having extremely high values. The highest fruit pulp/pit ratio measured in the variety Abou chawkeh confirmed that this variety is the best for table olive production.…”
Section: Discussionmentioning
confidence: 99%
“…Baladi, the most widespread variety in Lebanon, has been shown to have a large morphological variability . This variability is most likely the result of its broad geographical distribution throughout Lebanon, associated with different environmental conditions and cultural practices, and of clonal variation after years of domestication . Moreover, Baladi means ‘local’, that is, something autochthonous.…”
Section: Introductionmentioning
confidence: 99%
“…Olive production mainly occurs in the North (41%) and the South-Nabatiye (36%) [17]. Among all, 'Baladi' (that means local or autochthonous in Arabic language) is the most cultivated variety for its adaptation to the local climatic conditions and for its double use value [18][19][20][21][22]. 'Baladi', also known in many regions as 'Soury' (according to the Lebanese town of Tyre that means in Arabic language Sour), is characterized by a medium to high oil content (around 28% expressed on fresh weight basis) and has a low pulp to pit ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Kayu manglid banyak digunakan sebagai bahan konstruksi ringan, kayu pertukangan, kerajinan, perabot rumah tangga dan potensial sebagai baku industri pulp dan kertas (Siarudin, Sudomo, Indrjaya, Puspitojati, & Mindawati, 2016). Hingga saat ini, manglid menjadi jenis andalan setempat di Jawa Barat dan menjadi salah satu unggulan untuk hutan rakyat khususnya di wilayah Jawa Barat Bagian Timur (Rohandi & Gunawan, 2014;Winara, Hani, & Pieter, 2016;Indrjaya, 2016 dan Nuclea orientalis (Riany, Siregar, & Sudrajat, 2018 (Chalak et al, 2007;Sorkheh et al, 2010…”
unclassified